The Effect Of Implementation Of The Triple Elimination Program On Antenatal Care (ANC) In Pregnant Woman At Health Center In 2025 - yuli ana; Ida wati; Rizka Fauza; Irna Wati; Liani Sukmadewi Harahap (JOURNAL EDUCATIONAL OF NURSING(JEN), 2025)
The Triple Elimination program aims to prevent vertical transmission of HIV, syphilis, and hepatitis B from mother to child through the integration of routine screening in antenatal care (ANC) services. This program is in line with WHO's global commitment to eliminate the transmission of infectious diseases from mother to child that has the potential to have a long-term impact on infant health. The implementation of this program in primary service facilities such as health centers has a strategic role in improving early detection and proper management. This study aims to analyze the effect of program implementation on the quality of ANC services in Puskesmas. Using a quantitative approach with a cross-sectional design, the study involved 88 pregnant women as respondents. Data was obtained through a structured questionnaire that measured maternal satisfaction with aspects of services, such as accessibility, communication, physical examination, and information provided by health workers. Data analysis was performed by Chi-Square test, and the results showed a significant relationship between the implementation of the Triple Elimination program and the perception of ANC service quality (p = 0.013; OR = 2.7; 95% CI: 1.3–5.5). These results show that pregnant women who receive complete screening tend to be more satisfied with ANC services, because they feel comprehensively served. The implementation of Triple Elimination has a positive impact not only in the medical aspect but also in the psychological and emotional aspect, as it provides a sense of security against the potential transmission of serious diseases to the fetus. Suggestions are needed to strengthen the implementation of the program through improving laboratory infrastructure, the availability of reagents and logistics, continuous coaching for health workers, and intensive counseling to the community, so that the scope of the program is wider and more even. Cross-sector synergy and strong policy support are also key to the success of the program's sustainability